2016
DOI: 10.1371/journal.pone.0151266
|View full text |Cite
|
Sign up to set email alerts
|

Native Magnetic Resonance T1-Mapping Identifies Diffuse Myocardial Injury in Hypothyroidism

Abstract: Background and AimHypothyroidism (HT) is characterized by thyroid hormone deficiencies, which can lead to diffuse myocardial interstitium lesions in patients with HT. Myocardial longitudinal relaxation time (T1) mapping is a potential diagnostic tool for quantifying diffuse myocardial injury. This study aimed to assess the usefulness of T1 mapping in identifying myocardial involvement in HT, and determine the relationship between T1 values and myocardial function.MethodsA cross-sectional study was conducted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…More important, expansion of the collagen matrix increases the volume of distribution, leading to combined native T 1 augmentation . A previous study has revealed that T 1 values are significantly increased in patients with HT, particularly in cases with pericardial effusion . Furthermore, T 1 mapping has exploited slight changes in T 1 values to permit the measurement of early improvement after treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More important, expansion of the collagen matrix increases the volume of distribution, leading to combined native T 1 augmentation . A previous study has revealed that T 1 values are significantly increased in patients with HT, particularly in cases with pericardial effusion . Furthermore, T 1 mapping has exploited slight changes in T 1 values to permit the measurement of early improvement after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…10 This MRI sequence has been used already in a clinical setting and showed increased noncontrast T 1 values with impaired peak filling rate (PFR) in patients with newly diagnosed overt HT, which may reflect the presence of myocardial interstitial fibrosis, edema lesions, and then diastolic dysfunction in the low-FT3 heart. 11 Jellis et al have also confirmed that fibrosis is one of the important contributors to the pathogenesis of myocardial relaxation abnormalities. 12 In recent decades, the effects of levothyroxine treatment in patients with HT have mainly focused on myocardial structure and function according to the echocardiography or MRI using a late gadolinium enhancement imaging technique.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Global SRivr and SRe are primarily dependent on LV relaxation, while SRa, which occurs at late diastole, should be subject more to LV compliance. Compliance is influenced by myocardial stiffness and extracellular matrix, which has been detected in hypothyroidism using CMR . Therefore, the finding of a decreased late diastolic myocardial deformation (SRa) in untreated hypothyroidism is consistent with abnormal extracellular matrix alteration.…”
Section: Discussionmentioning
confidence: 70%
“…8 Compliance is influenced by myocardial stiffness and extracellular matrix, which has been detected in hypothyroidism using CMR. 23,24 Therefore, the finding of a decreased late diastolic myocardial deformation (SRa) in untreated hypothyroidism is consistent with abnormal extracellular matrix alteration.…”
Section: Discussionmentioning
confidence: 74%